Five New Cases of Megacystis-Microcolon-Intestinal Hypoperistalsis Syndrome (MMIHS), with One Case Showing a Novel Mutation. (4th August 2021) - Kalsbeek, Alyssa; Dhar-Dass, Renee; Hanan, Abdul; Al-Haddad, Eman; William, Iman; Alazraki, Adina; Poulik, Janet; McCollum, Kasey; Almashad, Aya; Shehata, Bahig M.
ABSTRACT: Background: Megacystis-microcolon-intestinal hypoperistalsis syndrome (MMIHS) is a lethal congenital disorder characterized by a large, non-obstructed bladder, microcolon, and lack of proper peristalsis. Materials and methods: Five cases of MMIHS were identified, confirmed histologically and were predominantly female (F:M, 4:1). DNA sequencing was also performed. Results: Four cases showed mutations in the α3 and β4 nicotinic acetylcholine receptor (ηAChR) subunits (CHRNA3 and CHRNB4, respectively) on chromosome 15q24. The 5th case had a delayed clinical presentation of intussusception at 11 months and showed a novel missense mutation in ATP2B4 on Chromosome 1q32. Conclusion: The first four patients showed a previously identified mutation. The 5th patient shows a novel mutation in ATP2B4. This novel gene was associated with a less severe presentation and increases success of multiorgan transplant than the other four patients. This highlights how identifying various mutations may impact prognosis and clinical treatment plans for MMIHS patients.